CHALLENGES AND OPPORTUNITIES IN THE DIGITAL TRANSFORMATION OF ISLAMIC EDUCATIONAL INSTITUTIONS - Arten H Mobonggi; Ritmon Amala; Muhammad Fadel Pulubuhu (LP2M IAIN Sultan Amai Gorontalo, 2023)
The purpose of this study is to analyze theories about digital transformation in Islamic educational institutions from the aspects of challenges and opportunities. The method used, namely the literature study approach, is used, which is the process of systematically elaborating and compiling several concepts about digital transformation in Islamic educational institutions. The focus of this research is to analyze theories about the challenges and opportunities of digital transformation in Islamic educational institutions. Reference sources are from journal articles, books, and other theories related to the focus of the content of the article title. The results of the study, namely the challenges and opportunities of digital transformation in Islamic educational institutions, cover financial challenges involving large initial investments, maintenance costs, and changes in business models. Curriculum challenges include teacher readiness, changes in teaching methods, material development, technology accessibility, understanding of Islamic values, evaluation, and resistance to change. On the other hand, digital transformation opportunities involve access to distance learning, improving the quality of learning with digital tools and utilizing data analytics. With technology, institutions can reach a wider target population and diversify their funding sources. Digital transformation can improve the accessibility of Islamic education and the financial sustainability of institutions